Surgical management of chronic fourth degree perineal tear: a single center experience - R, Ramesh Kumar; Chigateri, Seema; Kamat, Leena; Divya, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this article is to present the ridge about the recognition, preoperative management, surgical technique and long term follow up of patients with chronic fourth degree perineal tear. Methods: Authors conducted a prospective study in the department of obstetrics and gynecology in SDM hospital of medical sciences from 2008 January to 2016 December. Data on age, parity, incontinence to flatus, solid or liquids stools, duration of symptoms, history of previous repair, duration of repair, post-operative stay, complications and recovery were collected and analyzed. A total of thirty cases of chronic perineal tear were studied. Results: A total of 30 patients underwent CPT repair. Average duration of surgery was 90 minutes. 27 out of 30 patients were discharged on post-operative day 10. Three patients were non-compliant to treatment. Of the total 30 patients, two patients were lost for follow up. Overall success rate was 93% including patients who underwent re-surgery for failed repair. Conclusions: The significant finding of the present study was that a secondary repair of an anal sphincter injury was not associated with an unfavorable subjective outcome in relation to symptoms of anal incontinence. A good insight of perineal and anal sphincter anatomy and adherence to the sound principles is essential. The success rate in this study is 93.3% highlighting that a diligently performed operation by a surgeon of adequate expertise likely results in satisfactory outcome.